2009
DOI: 10.1002/14651858.cd006914.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Music during caesarean section under regional anaesthesia for improving maternal and infant outcomes

Abstract: The findings indicate that music during planned caesarean section under regional anaesthesia may improve pulse rate and birth satisfaction score. However, the magnitude of these benefits is small and the methodological quality of the one included trial is questionable. Therefore, the clinical significance of music is unclear. More research is needed to investigate the effects of music during caesarean section under regional anaesthesia on both maternal and infant outcomes, in various ethnic pregnant women, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
3
20
2
1
Order By: Relevance
“…Gold et al25 indicated that MT may help children with autistic spectrum disorder to improve their communicative skills. Laopaiboon et al26 indicated that music during planned cesarean section under regional anesthesia may improve pulse rate and birth satisfaction score. Bradt and Dileo27 reported that listening to music may have a beneficial effect on blood pressure, heart rate, respiratory rate, anxiety, and pain in persons with coronary heart disease.…”
Section: Resultsmentioning
confidence: 99%
“…Gold et al25 indicated that MT may help children with autistic spectrum disorder to improve their communicative skills. Laopaiboon et al26 indicated that music during planned cesarean section under regional anesthesia may improve pulse rate and birth satisfaction score. Bradt and Dileo27 reported that listening to music may have a beneficial effect on blood pressure, heart rate, respiratory rate, anxiety, and pain in persons with coronary heart disease.…”
Section: Resultsmentioning
confidence: 99%
“…Cohort studies and case series have reported the technical aspects and practitioner experiences with this procedure [10] and different groups have investigated the individual components of a "gentle" cesarean section. As such, there is some evidence that music at the time of cesarean section under regional anesthesia improves maternal satisfaction [14], and that early skin-to-skin contact at cesarean section decreases the time to breastfeeding initiation [15], and increases the chance for women to be breastfeeding at 1-4 months after delivery [16]. This study now also shows that maternal fear after childbirth is decreased, which may improve birth experiences in future pregnancies and could theoretically decrease the risk of postpartum depression.…”
Section: Parental Experiences Around C-sectionmentioning
confidence: 99%
“…Music therapy can reduce mean arterial pressure, anxiety and pain among women undergoing mastectomy for breast cancer (BinnsTurner et al, 2011). A study found that music during planned caesarean section under regional anaesthesia improved pulse rate and birth satisfaction scores (Laopaiboon et al, 2009). Music has been used as an alternate or complementary method for blood pressure stabilisation in patients undergoing cataract surgery (Merakou et al, 2015).…”
Section: Perioperative Settingmentioning
confidence: 99%